Apagamento e substituição de preposições na regência verbal do português falado na capital Luanda-Angola. - Binga, Lucas Kassoma (2025)
The main objective of this dissertation is to investigate the linguistic and sociocultural factors that influence the deletion and replacement of prepositions in the verbal government of Portuguese spoken in Luanda, identifying the most frequent prepositions in verbs of movement and indirect transitive verbs. To this end, we used the Theory of Linguistic Variation and Change, proposed by Weinreich, Labov and Herzog (2006 [1968]) and Labov (2008 [1972], to understand the linguistic and social aspects that interfere in these phenomena, having analyzed 52 interviews with participants who have Portuguese as their mother tongue (L1) or as a second language (L2). Of these, 26 are male and 26 are female, distributed in age groups, levels of education and mother tongue. The interviews belong to a research project with data collected in Angola, called “In Search of the Roots of Brazilian Portuguese”, based at the State University of Feira de Santana (UEFS). The results point to the erasure and replacement of prepositions as a characteristic phenomenon of Luandan Portuguese, that is, the prepositions de governed by the verb gosta and a by the verb assistir are erased in some contexts, and the preposition para and em replace the preposition a in verbs of movement, mainly when it comes to the verbs ir, vir and chegar. These results shed light on the complex sociolinguistic dynamics of the Portuguese variety and allow us to establish connections with the socio-historical context of Angolan Portuguese, leading to a framework of verbal regency that moves away from European Portuguese (EP), establishing its own configuration, resulting from the interference of Bantu languages and the process of irregular linguistic transmission (Lucchesi; Baxter, 2009). At the same time, there is a tendency to approach the Brazilian variety (Undolo, 2015; Adriano, 2014; Silva; Araújo, 2018; Petter, 2007).